2022
DOI: 10.1111/clr.14020
|View full text |Cite
|
Sign up to set email alerts
|

Implant failure and associated risk factors of transcrestal sinus floor elevation: A retrospective study

Abstract: Implant-supported prosthesis has become a common and reliable treatment for fully or partially edentulous patients (Howe et al., 2019).However, rehabilitation of the posterior maxilla is challenging under most circumstances due to not only insufficient residual bone height (RBH), but also poor bone quality (Al-Dajani, 2016). To tackle this problem, several treatment options have been proposed, among which sinus floor elevation (SFE) is the most commonly used approach at present (Al-Moraissi et al., 2018;Antono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…To date, there is no clear threshold in RBH proving critical for implant survival. According to a 3‐year retrospective study by Li et al (2023), RBH ≤ 6 mm and male sex were associated with a significantly increased late failure rate of implant after trans‐crestal sinus floor augmentation. Ha et al (2020), in a 10‐year follow‐up study, indicated that the rate of implant failure increased with a decrease in RBH ≤ 5 mm, but was not affected by RBH > 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no clear threshold in RBH proving critical for implant survival. According to a 3‐year retrospective study by Li et al (2023), RBH ≤ 6 mm and male sex were associated with a significantly increased late failure rate of implant after trans‐crestal sinus floor augmentation. Ha et al (2020), in a 10‐year follow‐up study, indicated that the rate of implant failure increased with a decrease in RBH ≤ 5 mm, but was not affected by RBH > 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Sex has been reported to be associated with implant survival in the sinus augmentation technique 9,26 . However, this correlation might be derived from the confounding effect of the smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…Sex has been reported to be associated with implant survival in the sinus augmentation technique. 9,26 However, this correlation might be derived from the confounding effect of the smoking habit. In our study, we detected an adverse effect of smoking habit on the survival curves but did not find a significant effect of sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the original residual alveolar ridge height was one of the important factors in determining which SFA program to operate (Starch‐Jensen & Jensen, 2017). TSFA technique has been commonly used in cases with a residual bone height (RBH) >6 mm (Li et al, 2023). However, for cases of less than 6 mm RBH, the current expert consensus tends to recommend the lateral approach as a highly predictable and reliable approach to augment the atrophic posterior maxilla (Jepsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%